Relationship Between Q-Angle and Articular Cartilage in Female Patients With Symptomatic Knee Osteoarthritis: Ultrasonographic and Radiologic Evaluation - Ayşe Aydemir EKİM and Hatice HAMARAT and Ahmet MUSMUL (Archives of Rheumatology, 2017)
Objectives: This study aims to examine the association between Q-angle and clinical, radiological, and ultrasonographic findings in patients with knee osteoarthritis (OA). Patients and methods: Sixty-eight female patients (mean age 59.8±6.8 years; range 39 to 78 years) diagnosed with knee OA were included in this study and classified into two groups according to Q-angle of symptomatic knees: low Q-angle group (LQ) (n=40) and high Q-angle group (HQ) (n=28) (LQ-angle <15° and HQ-angle ≥15°, respectively). Patients were clinically assessed for pain and functional status by using a visual analog scale and the Western Ontario and McMaster Universities Arthritis Index. X-rays of knees were scored using the Kellgren-Lawrence OA grading system. Symptomatic knees were also evaluated using ultrasonography for distal femoral cartilage thickness/grading. Results: No significant difference was observed in clinical and imaging findings between the groups (p>0.05). HQ-angle measurements were positively correlated with cartilage grading by ultrasonography (r=0.435, p=0.033) and Kellgren-Lawrence grading system (r=0.435, p=0.021), and negatively correlated with cartilage thickness measurements of the medial femoral condyle (r=-0.399, p=0.036). Conclusion: We found that HQ-angle was associated with cartilage thickness measurements of the medial femoral condyle and cartilage grading by ultrasonography and the Kellgren-Lawrence grading system in patients with knee OA.